Microplastics in Aquatic and Terrestrial Sediments: Occurrence, Analytical Techniques, Environmental Interactions, and Ecotoxicological Implications - Dr. Alejandro M. Ríos (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
Microplastic pollution has emerged as one of the most complex and persistent environmental challenges of the twenty-first century, driven by the exponential growth of plastic production and the inefficiency of global waste management systems. While early research predominantly focused on floating plastic debris in marine surface waters, growing scientific attention has shifted toward sediments, soils, freshwater systems, and food matrices, where microplastics accumulate, interact with contaminants, and exert long-term ecological effects. This article presents an extensive and critical synthesis of existing research on microplastics in sediments and related environmental compartments, drawing exclusively on established peer-reviewed literature. The review elaborates on the sources and formation pathways of microplastics, their spatial distribution across marine, freshwater, agricultural, and remote environments, and the physicochemical processes governing their environmental behavior. Particular emphasis is placed on analytical and extraction techniques, including density separation, spectroscopic identification, and emerging imaging-based approaches, highlighting their strengths, limitations, and methodological uncertainties. Furthermore, the article explores the role of microplastics as vectors for heavy metals and organic pollutants, examining sorption mechanisms, competitive interactions, and implications for contaminant bioavailability. Ecotoxicological evidence from laboratory bioassays and field observations is discussed in depth to elucidate biological responses across trophic levels. By integrating occurrence data, methodological advancements, and ecological impacts, this work identifies critical knowledge gaps and conceptual challenges that hinder risk assessment and management strategies. The analysis underscores the necessity of harmonized methodologies, interdisciplinary research frameworks, and context-specific remediation strategies to address microplastic pollution in sediments and associated ecosystems. Ultimately, this article contributes to a deeper theoretical understanding of microplastics as dynamic environmental contaminants and provides a foundation for future research and policy development.